APPLICATION OF SOFTWARE SIMULATION FOR LIGHTING ANALYSIS IN THE LAB. OF HOTEL OPERATIONS DEPARTMENT UMN - Saputri, Fahmy Rinanda; Paramasatya, Johanes Dimas; Radithya, Linus Gregorius (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
In this study, an analysis of lighting in campus buildings was conducted, specifically for the in the Laboratory of Hotel Operations Department Universitas Multimedia Nusantara (UMN). The main issue identified is visual comfort for occupants in a room, which must comply with the Indonesian National Standard (SNI) 6197-2020. Ensuring proper lighting is crucial for both functionality and occupant comfort, particularly in educational settings where tasks require adequate illumination. The lighting analysis was performed through simulation using Dialux and SketchUp software. The process involved designing a detailed building model based on the room layout, including all relevant architectural and interior features. Once the model was completed, the lighting simulation was executed using Dialux. This simulation entailed determining the optimal position of furniture within the room, selecting appropriate types of luminaires, and strategically placing these luminaires to achieve the desired lighting levels. The results of the simulation indicated that the current lighting levels in the laboratory were below the standards set by the SNI. Specifically, the minimum illumination level required by SNI 6197-2020 for a room functioning as a restaurant kitchen, which is analogous to the that Laboratory, is an average of at least 250 lux. The findings highlight the need for redesigning the lighting system in the laboratory to meet the prescribed standards and ensure adequate visual comfort and functionality for its users.